Embedded Connector in Severe Optimization of Steel Plate for Shear Strengthening of RC Beam: Experimental and Numerical Investigations - Md. Ashraful Alam; Suliman A. Bakkar; Shahnawaz A. Onik; Kamal N. Mustapha (Advances in Civil Engineering)
Environmental impact has become one of the major factors taken into consideration for recent civil engineering studies and projects. Thus, researchers have been concentrating on shear strengthening of existing reinforced concrete structure as an upgrade method instead of demolishing and reconstructing. In general, shear strengthening of RC beams using externally bonded steel plate has gained huge popularity. However, premature debonding of plates is the main drawback of the system, which could be mitigated using embedded connector; thus, the dimension of steel plate could be reduced significantly. Furthermore, numerical analysis on shear strengthening of beams using embedded connector would provide a great insight on the structural behavior. The aim of this research is to severely reduce the dimension of the steel plate using embedded connector for shear strengthening of RC beams and to investigate the performances of optimized shear-strengthened beams through experimental and numerical investigations. The results showed that the dimension of plate was reduced without debonding of the plate if the beam was designed for shear strengthening with the consideration of yield strength of steel plate and shear link. Experimental results showed a maximum increase in failure of 24%. The numerical results predicted accurately the structural performance of beams. The embedded connector had a great effect in deferring and minimizing the debonding failure and accordingly increasing the maximum load of shear failure between 14.5% and 24% compared to control beam.